Mapping The Potential of Mangrove Planting in The Rehabilitation of Coastal Ecosystems Using Drone Technology - Ayub, Ayub Sugara; Ari Anggoro; Agung Hasan Lukman; Ana Ariasari; An Nisa Nurul Suci; Nella Tri Agustini; Feri Nugroho; Ali Muhammad Muslih; Cindy Claudea Hanami; Rifi Zulhendri (Journal of Sylva Indonesiana, 2023)
Mangroves, as one of the vegetation types that is a natural stronghold from coastal disasters, also function as a shelter and find food for various biota in coastal ecosystems. Therefore, protecting the mangrove ecosystem from degradation is very important. One effort that needs is ecosystem rehabilitation through mangrove planting in coastal environments. To support it, a design was devised using drones and remote-sensing vehicles to assist in making mangrove planting designs. This research was conducted in Jenggalu Estuary, Gading Cempaka District, Bengkulu City. This research aims to study the use of drones in mapping potential mangrove planting areas and designing a mangrove planting plan to rehabilitate coastal ecosystems. In mapping using drones, the height used was 80 meters with 80% overlap, and 2.87 hectares of potential mangrove planting area was obtained. Based on the research results, drones in mapping are very useful in calculating the area of potential mangrove planting areas and designing effective planting plans. There are four scenarios for planting mangroves with a spacing of 0.5 m, 1 m, 2 m, and 3 m, respectively. For a planting area of 2.87 ha, the number of seeds needed is 114,800 planting points for a distance of 0.5 m, 28,700 planting points for a distance of 1 m, 7,175 planting points for a distance of 2 m, and 3,189 planting points for a distance of 3 m